Dietary intervention rescues myopathy associated with neurofibromatosis type 1. (8th December 2017) - Summers, Matthew A; Rupasinghe, Thusitha; Vasiljevski, Emily R; Evesson, Frances J; Mikulec, Kathy; Peacock, Lauren; G R Quinlan, Kate; Cooper, Sandra T; Roessner, Ute; Stevenson, David A; Little, David G; Schindeler, Aaron
Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant genetic disorder with complex symptomology. In addition to a predisposition to tumors, children with NF1 can present with reduced muscle mass, global muscle weakness, and impaired motor skills, which can have a significant impact on quality of life. Genetic mouse models have shown a lipid storage disease phenotype may underlie muscle weakness in NF1. Herein we confirm that biopsy specimens from six individuals with NF1 similarly manifest features of a lipid storage myopathy, with marked accumulation of intramyocellular lipid, fibrosis, and mononuclear cell infiltrates. Intramyocellular lipid was also correlated with reductions in neurofibromin protein expression by western analysis. An RNASeq profile of Nf1 null muscle from a muscle-specific Nf1 knockout mouse ( Nf1 MyoD − / − ) revealed alterations in genes associated with glucose regulation and cell signaling. Comparison by lipid mass spectrometry demonstrated that Nf1 null muscle specimens were enriched for long chain fatty acid (LCFA) containing neutral lipids, such as cholesterol esters and triacylglycerides, suggesting fundamentally impaired LCFA metabolism. The subsequent generation of a limb-specific Nf1 knockout mouse ( Nf1 Prx 1 − / − ) recapitulated all observed features of human NF1 myopathy, including lipid storage, fibrosis, and muscle weakness. Collectively, these insights led to the evaluation of a dietary intervention of reduced LCFAs, and enrichment of medium-chain fatty acids (MCFAs) with L-carnitine. Following 8-weeks of dietary treatment, Nf1 Prx 1 − / − mice showed a 45% increase in maximal grip strength, and a 71% reduction in intramyocellular lipid staining compared with littermates fed standard chow. These data link NF1 deficiency to fundamental shifts in muscle metabolism, and provide strong proof of principal that a dietary intervention can ameliorate symptoms.